Counting the Countless: Bacterial Quantification by Targeting rRNA Molecules to Explore the Human Gut Microbiota in Health and Disease - Tsuji, Hirokazu; Matsuda, Kazunori; Nomoto, Koji (Frontiers in Microbiology, 2018)
Over the past decade, the advent of next-generation-sequencing tools has revolutionized our approach to understanding the human gut microbiota. However, numerical data on the gut bacterial groups—particularly low-cell-count microbiota, such as indigenous pathobionts, that are otherwise important components of the microbiota—are relatively limited and disparate. As a result, the comprehensive quantitative structure of the human gut microbiota still needs to be fully defined and standardized. With the aim of filling this knowledge gap, we have established a highly sensitive quantitative analytical system that is based on reverse transcription—quantitative PCR and targets microbial rRNA molecules. The system has already been validated in the precise, sensitive, and absolute quantification of more than 70 target bacterial groups belonging to various human gut bacterial clades, including predominant obligate and facultative anaerobes. The system demonstrates sensitivity several hundred times greater than that of other rRNA-gene-targeting methods. It is thus an efficient and valuable tool for exhaustive analysis of gut microbiota over a wide dynamic range. Using this system, we have to date quantified the gut microbiota of about 2,000 healthy Japanese subjects ranging in age from 1 day to over 80 years. By integrating and analyzing this large database, we came across several novel and interesting features of the gut microbiota, which we discuss here. For instance, we demonstrated for the first time that the fecal counts of not only the predominant bacterial groups but also those at lower cell counts conform to a logarithmically normal distribution. In addition, we revealed several interesting quantitative differences in the gut microbiota of people from different age groups and countries and with different diseases. Because of its high analytic sensitivity, the system has also been applied successfully to other body niches, such as in characterizing the vaginal microbiota, detecting septicemia, and monitoring bacterial translocation. Here, we present a quantitative perspective on the human gut microbiota and review some of the novel microbial insights revealed by employing this promising analytical approach.